Socially responsible investing through the equity funds in the global ownership network. - Takayuki Mizuno (Public Library of Science (PLoS), 2021)
We analyze the connectivity of equity investments to the firms in the global ownership network that are reported as non-compliant with Environment, Social, and Government (ESG) benchmarks. We find that a large number of shareholders have ownership linkages to non-ESG firms, most commonly with three or four degrees of separation. Analyzing the betweenness centrality for shareholders connecting the ultimate owners and non-ESG firms, we find that the investment management companies play important roles in channeling the investment money into non-ESG firms, where largest American asset managers commonly have one to two degrees of separation on their ownership linkages to those problematic firms. Since asset managers collect capital from investors by running the equity funds, we analyze the ownership stakes and the associated voting rights attributable to the equity funds investors. We estimate the distribution of the power of corporate control over non-ESG firms among specific asset managers (such as BlackRock and Fidelity) and among different types of the equity funds (such as mutual funds and exchanged-traded funds), and explores how investing in the equity funds rather than ownership investing may have shifted the distribution of the power to control those non-ESG firms.